Evolving localization patterns of company foundations - Evidence from the German MST-industry - Tobias Scholl; Thomas Brenner; Martin Wendel (Philipps-University Marburg, Department of Geography, 2012)
We investigate company foundations in the German micro technology industry by means of a spatial-temporal micro-geographic analysis. In order to deal with our unusual detailed data, we develop a new distance-based framework for a logistic regression that is able to present results in a continuous space. Locations of company foundations are investigated with respect to their spatial proximity to similar firms, patent owner, related industries and research institutions and are benchmarked with the overall distribution of company foundations in Germany. We demonstrate that spatial proximity has a clear influence on where new companies are founded. Furthermore, the influence of proximity to different agents is not constant over times but evolves with the industry's life cycle.
Keywords: C40; M13; R12; 330; Spatial concentration; localization; clusters; MAUP; distance-based measures